Social Citizenship in the Context of Europeanization and Growing Inequalities: An Empirical Contribution to the Theoretical Debate - Leonardi, Laura; Scalise, Gemma (SocietàMutamentoPolitica, 2016)
The political and economic crisis of Europe and the austerity programs within EU countries have brought back to center the issues of inequality and social justice in Europe that during the Twentieth century have been addressed through the institutionalization of social citizenship. Europeanization and globalization challenge social cohesion and alters the basic institutions on which social citizenship was constructed in welfare societies. Starting from the results of an empirical study, the aim of this article is to give new impulses to the theoretical reflection on social citizenship as a distinct issue, although related with the concept of citizenship. The focus of the analysis is on members of transnational civil society organizations and their ideas and practices enhancing new forms of a more inclusive and sustainable social citizenship. Conclusions discuss how social bonds and solidarity are reframed transnationally across national, regional, European and global borders, and the implications of this process for the reformulation of the concept of social citizenship.